Overview of structural mechanical investigations on additively manufactured medical products. Issue 2 (30th April 2018) - Schramm, Britta; Risse, Lena; Brüggemann, Jan-Peter; Richard, Hans Albert; Kullmer, Gunter
The article provides an overview of some applications of additive manufacturing in medical technology and discusses from an engineering and structural mechanical point of view the different areas of expertise to construct medical devices in a lifetime-oriented, stress-tolerant and patient-specific manner. In addition, structural mechanical investigations are illustrated by selected projects that were initiated among others by local supply healthcare stores and disabled facilities. The development and additive manufacturing of patient-specific, strength- and stiffness-optimized, and fracture-safe medical devices requires knowledge from various areas of expertise. In order to attain the mentioned objectives influence factors as well as a variety of areas of expertise have to be considered. Some of these factors and areas are covered in this article.